PROSES PENEGAKAN HUKUM PIDANA TERHADAP PELAKU TINDAK PIDANA PENCURIAN DATA NASABAH BANK MELALU MESIN ATM SEBAGAI PENYALAHGUNAAN TEKNOLOGI KOMUNIKASI DAN INFORMASI (STUDI PUTUSAN NOMOR 204/Pid.Sus/2021/PN.Pdg) - Roni Roni; Lola Yustrisia; Syaiful Munandar (Ensiklopedia of Journal, 2023)
Advances in information technology, especially in the field of computers and the internet have proven to have a positive impact on the progress of human life. With the development of information technology, it is able to change patterns of thinking about boundaries, time, values, forms of objects, logic of thinking, work patterns and boundaries of social behavior from manual to computerized or digital. Information technology has become a major industry and is able to meet the most basic needs in the economic field as well as other key resources. As well as with the development of information technology, various forms of criminal acts or crimes occur through digital media as cybercrimes. All criminal acts can be easily and effectively carried out by utilizing advances in information technology. One of the crimes that occurs using information technology advances is the theft of personal data. If a cybercrime occurs against misuse of information technology, then criminal sanctions can be applied based on Law Number 11 of 2008 concerning Information and Electronic Transactions and Law Number 19 of 2019 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions.